2017
DOI: 10.1016/j.jallcom.2016.11.217
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of coherent interfaces of Laves-phase MgZn2 and stability of thin MgZn2 layers in Mg-Zn alloys

Abstract: The β 1 ′and β 2 ′ are important precipitates in Mg-Zn alloys. Two types of precipitates both are composed of MgZn 2 , but the orientation relationships of MgZn 2 with the α-Mg matrix in two precipitates are different. To understand the properties of β 1 ′and β 2 ′, we use the first-principles method to perform a systematical investigation of coherent interfaces of β 1 ′/α-Mg and β 2 ′/α-Mg. Here, we present exhaustive analysis of the structure and stability for these interfaces, and find that the interfacial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The selected area electron diffraction (SAED) proves that these particles are MgZn 2 (Fig. 3b and c), which has been widely reported in the previous studies [25,26]. The appearance of fine MgZn 2 phase is related to the dynamic precipitation during the reduplicative MDF process, because the homogenization treatment easily results in the supersaturation state of Zn elements in α-Mg matrix.…”
Section: Microstructuresupporting
confidence: 70%
“…The selected area electron diffraction (SAED) proves that these particles are MgZn 2 (Fig. 3b and c), which has been widely reported in the previous studies [25,26]. The appearance of fine MgZn 2 phase is related to the dynamic precipitation during the reduplicative MDF process, because the homogenization treatment easily results in the supersaturation state of Zn elements in α-Mg matrix.…”
Section: Microstructuresupporting
confidence: 70%
“…The covalent, ionic and metallic bonding characteristics of the MgZn 2 phase have been discussed by several authors. 41,42 Much of the pioneering work on the dealloying of binary alloys has focused on alloys of noble elements and the Zn-Cu system. The importance of elemental composition on the critical potential, E c , for the dealloying of binary alloys has been suggested by different authors.…”
Section: Discussionmentioning
confidence: 99%
“…The lattice constants are a = b = 0.5221 nm, c = 0.8567 nm, α = β = 90°, γ = 120°, and the total number of atoms in the unit cell is 12. Related studies have shown that MgZn 2 phase was a common Mg-Zn strengthening phase, which played an important role in improving the mechanical properties of magnesium alloys [32].…”
Section: Resultsmentioning
confidence: 99%